Influence of Auditor Professionalism and Competence on the Quality of Internal Audit - Ari Bramasto; Indri Utami; Ayu Lestari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This thesis entitled "The Effect of Professionalism and Auditor Competence on the Quality of Internal Audit Study at the Bandung Regency Housing, Settlement and Land Office" this research is a quantitative research, which aims to find out: 1) The magnitude of the influence of auditor professionalism on the quality of internal audit, 2) The magnitude of the influence of auditor competence on the quality of internal audit, and 3) The magnitude of the influence of audit quality on the quality of internal audit. The sampling technique used was the distribution of questionnaires with a total of 30 respondents.Tests conducted in this study include validity tests, reliability tests, classical assumption tests (normality tests, heteroscedasticity tests and, multicolonicity tests), simple linear regression, determination coefficient tests and t tests processed using the help of SPSS (Statistical Product and Service Solutions) software for Windows version The results of this study show that 1) There is an influence of auditor professionalism on the quality of internal audit. 2) There is an influence of auditor competence on the quality of internal audit. 3) There is an effect of audit quality on the quality of internal audit.